2019
DOI: 10.1159/000496453
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab Dose-Escalation Therapy Is Effective in Refractory Crohn’s Disease Patients with Loss of Response to Adalimumab, Especially in Cases without Previous Infliximab Treatment

Abstract: Background/Aims: Adalimumab dose escalation is one of the most important options in refractory Crohn’s disease patients with loss of response to adalimumab. The goal of this study was to evaluate the effectiveness of adalimumab dose escalation in Crohn’s disease patients with loss of response to adalimumab, since there are few reports of adalimumab dose escalation, especially in East Asia. Methods: The clinical response to adalimumab dose escalation in Crohn’s disease patients with loss of response to adalimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Sustained clinical response and remission beyond 12 months from the time of dose escalation were reported in 14 studies and ranged from 33% to 90% for response and 28%‐81% for remission 27,31,33‐36,41,42,45‐48,50,51 . Similar rates of loss of response to dose‐escalated treatment (tertiary loss of response) were reported across five studies 27,30,44,45,52 .…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Sustained clinical response and remission beyond 12 months from the time of dose escalation were reported in 14 studies and ranged from 33% to 90% for response and 28%‐81% for remission 27,31,33‐36,41,42,45‐48,50,51 . Similar rates of loss of response to dose‐escalated treatment (tertiary loss of response) were reported across five studies 27,30,44,45,52 .…”
Section: Resultsmentioning
confidence: 68%
“…32 Sustained clinical response and remission beyond 12 months from the time of dose escalation were reported in 14 studies and ranged from 33% to 90% for response and 28%-81% for remission. 27,31,[33][34][35][36]41,42,[45][46][47][48]50,51 Similar rates of loss of response to dose-escalated treatment (tertiary loss of response) were reported across five studies. 27,30,44,45,52 In the study by Ma et al, 30 over half (56.8%) of those that responded clinically to escalated adalimumab subsequently lost response (median time to tertiary loss of response 47.9 weeks [IQR 24.7-80.3]).…”
Section: Standard Maintenance Dosing Of Infliximab and Adalimumabmentioning
confidence: 84%
See 2 more Smart Citations
“…This shows no relevant differences with the previous data and constitutes one main finding of our study: dose escalation was needed more often in patients with prior anti-TNF use. In fact, the vast majority of the included studies evaluating both naïve and non-naïve patients showed a greater incidence in the loss of response in those non-naïve [ 30 , 34 , 35 , 60 , 81 , 84 , 111 , 121 , 132 , 161 , 163 , 168 , 192 , 193 ].…”
Section: Discussionmentioning
confidence: 99%